Analysis of the Tools for Evaluating Embodied Energy Through Building Information Modeling Tools: A Case Study of a Single-Unit Shell Building - Andrzej Szymon Borkowski; Urszula Hajdukiewicz; Julia Herbich; Kalina Kostana; Anna Kubala (Earth)
Today, the construction sector is largely responsible for climate change and global warming. The industry generates the largest carbon footprint and is also one of the least digitized industries in national economies. Faced with the challenge of reducing this carbon footprint, BIM is becoming an essential tool for building digital twins, which in turn makes it possible to calculate and track the carbon footprint over time for designed, constructed, and existing buildings. Semantically rich databases such as BIM make it possible to record the past, present, and future states of buildings and infrastructure facilities. To date, primary research using the free and popular UrbanBIM tool has been conducted on ready-made models, e.g., a previously prepared piece of space. In this secondary study, a specific pre-designed shell building in the BIM environment was examined, and the embedded carbon footprint was calculated for it. The calculated result of 76.35 tons of CO2 provides an overview of the solutions used and an analysis of the various elements in terms of their environmental impact. The results of the study indicate a growing need to automate the modeling of building information for analysis and simulation, and then to further manage the information. The paper also identifies limitations and presents future research directions for carbon footprint calculation and tracking.